2022
DOI: 10.1021/acs.molpharmaceut.2c00465
|View full text |Cite
|
Sign up to set email alerts
|

Oral Nanocurcumin Alone or in Combination with Insulin Alleviates STZ-Induced Diabetic Neuropathy in Rats

Abstract: Diabetes mellitus (DM), a multifaceted metabolic disorder if not managed properly leads to secondary complications. Diabetic peripheral neuropathy (DPN) is one such complication caused by nerve damage that cannot be reversed but can be delayed. Recently, diabetes patients are using dietary supplements, although there remains a general skepticism about this practice. Curcumin (CUR), one such supplement can help prevent underlying low-grade inflammation in diabetes, but it is plagued by poor oral bioavailability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…The FTIR spectra confirmed the presence of amide linkage­(1630 cm-1) in PLGA-GA2 (Figure S1B). Subsequently, CUR-laden PLGA-GA 2 nanoparticles (nCUR) were made on a large scale and freeze-dried following our published protocols. The z -average size of nCUR was ∼270 (PDI ∼0.25) (Figure S1C) with ∼0.112 mg of CUR entrapped/mg of PLGA-GA 2 , and particles are spherical in shape (Figure S1D).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The FTIR spectra confirmed the presence of amide linkage­(1630 cm-1) in PLGA-GA2 (Figure S1B). Subsequently, CUR-laden PLGA-GA 2 nanoparticles (nCUR) were made on a large scale and freeze-dried following our published protocols. The z -average size of nCUR was ∼270 (PDI ∼0.25) (Figure S1C) with ∼0.112 mg of CUR entrapped/mg of PLGA-GA 2 , and particles are spherical in shape (Figure S1D).…”
Section: Resultsmentioning
confidence: 99%
“…Earlier, we demonstrated that nCUR with or without long-acting insulin alleviates STZ-induced diabetic peripheral neuropathy or diabetic kidney disease in rats by modulation of the inflammatory cascade. 24,40 Herein, we have identified an additional role for this potential combination in preventing diabetic retinopathy by inhibiting Piezo1 in the ganglion cell (GCL) and photoreceptor layers.…”
Section: Discussionmentioning
confidence: 99%
“…This arrangement introduces numerous pendant carboxylic acid groups along the polymeric backbone . We further demonstrated conjugating a small molecule ligand on P2s; gambogic acid (GA) binds noncompetitively to transferrin receptors. The linker used in these studies was a short ethylenediamine (2C), effectively conjugating the GA to P2s (Figure ). Ethylenediamine has been utilized as a linker in diverse applications, particularly on the surface of nanoparticles. , …”
Section: Resultsmentioning
confidence: 92%
“…Dynamic light scattering (DLS) revealed nanoparticle sizes in the range of approximately 260–290 nm, with zeta potentials > ±20 mV, indicative of stable emulsions and therefore less likely to aggregate (Table ). Furthermore, we have previously shown that GA-decorated nanoparticles in this size range are appropriate for oral absorption. , …”
Section: Resultsmentioning
confidence: 98%
“…Hence, Cur, with its anti-inflammatory and antioxidant properties, has become a promising candidate drug for the treatment of inflammatory diseases. Nonetheless, the therapeutic activity of Cur is limited due to its poor water solubility, fast biological metabolism, and poor bioavailability [ 24 , 25 , 26 , 27 ]. The dose or frequency of administration must be increased to achieve the desired therapeutic effects, which in turn cause adverse reactions to the body.…”
Section: Introductionmentioning
confidence: 99%